Pengaruh Kualitas Produk, Promosi dan Harga Terhadap Keputusan Pembelian Produk Lacoco en Nature - Agita, Nur; Meliana, Vina (Research and Community Service UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of product quality, promotion and price on purchasing decisions for Lacoco en Nature products. This study uses a quantitative approach. The sampling technique was purposive sampling through distributing questionnaires to 165 who had seen the content of local skincare brand Tiktok, and had used Lacoco en Nature stain or scar removal products. Data processing techniques in this study using multiple linear regression test. The results of the study indicate that product quality affects purchasing decisions, promotions affect purchasing decisions, and price affects purchasing decisions.